How to reform pension reforms… and the cost of not doing it - Zubiri, Ignacio (Cuadernos de Relaciones Laborales, 2015)
The Spanish pension system will be balanced reducing pensions. As a result, the initial pension will lower and the retirement period will be smaller. Furhermore, due to the Index for Pension Revaluation, in the medium and even in the long run the real value of pensions will decrease continuously. All this, assumes that future pensioners don´t have any rights and that they have to bear all the cost of ageing. In the end, this will lead to a society aged and impoverished. To avoid that and respect the rights of pensioners, a new reform is needed. This reform has to eliminate some of the measures taken and increase the resources of the system (taxes and other resources).